Review of micronutrients in Sokoto, Nigeria: Insufficiency and effects on brain (Nervous system) functioning - Yusuf Sarkingobir (Journal of Emerging Science and Engineering, 2025)
In humans, micronutrients are special nutrients that are supposed to be obtained from diets in small amounts to aid body functioning, growth, and development. Micronutrients deficiency results due to low dietary nutrients intake and is currently a worldwide threat that affects humans in various ways, including learning or brain functioning. Sokoto State Nigeria due to its peculiarities such as arid land, poverty, poor education, single-diet nutrition, etc. should be of great risk of micronutrients deficiencies. The objective of this review paper is concerned about micronutrients deficiencies with regards to Sokoto State Nigeria and consequences on brain function. Micronutrients prevalence in Sokoto Nigeria, micronutrients in foods, insufficiency of nutrients in soil, consequences of excess micronutrients, micronutrients deficiencies, causes, etc. were described. Multifold approach to this myriad task should be put forward and tackled head-on; otherwise, the society (Sokoto) will languish continuously with maternal and child mortalities, abnormalities, mental derangements, aa well as poor productivity..